2012
DOI: 10.1155/2012/108163
|View full text |Cite
|
Sign up to set email alerts
|

Neonatally Induced Mild Diabetes in Rats and Its Effect on Maternal, Placental, and Fetal Parameters

Abstract: The aim of this study was to assess placental changes and reproductive outcomes in neonatally induced mild diabetic dams and fetal development in their offspring. At birth, female rats were assigned either to control or diabetic group (100 mg of streptozotocin/Kg, subcutaneously). At adulthood, the female rats were mated. During pregnancy, the blood glucose levels and glucose and insulin tolerance tests were performed. At term, maternal reproductive outcomes, fetal and placental weight, and placental morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 43 publications
4
25
1
1
Order By: Relevance
“…Despite placentomegaly, decreases in placental blood flow in parallel with fetal growth retardation have been previously reported as a result of increased erythropoietin and secondary polycythemia caused by hypoxia in the fetus. A similar pattern of fetal growth retardation caused by decreased placental blood flow has been correlated with placentomegaly in pregnant women living at high altitudes and using alcohol (6). In this study, histologically distinctive differences were detected in the placenta of diabetic rats with respect to rats in the control group.…”
Section: Discussionsupporting
confidence: 74%
“…Despite placentomegaly, decreases in placental blood flow in parallel with fetal growth retardation have been previously reported as a result of increased erythropoietin and secondary polycythemia caused by hypoxia in the fetus. A similar pattern of fetal growth retardation caused by decreased placental blood flow has been correlated with placentomegaly in pregnant women living at high altitudes and using alcohol (6). In this study, histologically distinctive differences were detected in the placenta of diabetic rats with respect to rats in the control group.…”
Section: Discussionsupporting
confidence: 74%
“…Nevertheless, a number of studies carried out in our laboratory found increased rates of pre-and postimplantation embryo losses and embryonic death (resorption), reduced number of live fetuses, and maternal weight gain during diabetic pregnancy. These alterations are due to metabolic changes caused by hyperglycemic peaks during pregnancy (Kiss et al 2009;Damasceno et al 2011;Iessi et al 2010;Saito et al 2010;Dallaqua et al 2012;Sinzato et al 2012). The divergent results shown in our study, which does not reinforce an effect of diabetes on the reproductive performance of rats, is possibly explained by mating time.…”
Section: Discussioncontrasting
confidence: 81%
“…In addition, diabetes causes intrauterine growth restriction (IUGR), reduces the number of corpus luteum and embryo implantation, and increases the rates of pre-and postimplantation embryo losses (Sinzato et al 2012). Iessi et al (2010) found intrauterine growth restriction (IUGR) in fetuses from rats with induced mild diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…before glucose administration. Blood glucose concentrations were measured at 0 (previous administration of glucose solution/plant extractfasting glucose), 30, 60 and 120 min (Mello et al 2001, Sinzato et al 2012. Glucose responses during the OGTT were evaluated by estimation of the total area under the curve (AUC), using the trapezoidal method (Tai 1994).…”
Section: Biochemical Profile Analysismentioning
confidence: 99%